APPLICATION OF NEURAL NETWORKS IN SYSTEMS OF AUTOMATIC REGULATION OF TECHNOLOGICAL PROCESSES OF GRINDING (Conferencea, 2023)
This paper discusses the parameters used to automate and control the grinding and classification process and the capabilities of neural networks. It also analyzes a number of properties useful from the point of view of practical use of neural networks.